TRAINING FOR MAKING GINGER AND TEMPE FOOD BARS AS PREVENTIVE PRODUCTS DURING COVID-19 ENDEMY AT THE STUDENT ASSOCIATION OF PUBLIC HEALTH AND NUTRITION INSTITUT KESEHATAN MEDISTRA LUBUK PAKAM - Raini Panjaitan; Reno Irwanto; Risda Situmorang (JURNAL PENGMAS KESTRA (JPK), 2022)
Currently, the spread of COVD-19 can be directly transmitted between humans, resulting in an extraordinary number of cases throughout 2022 until now. The condition of Covid-19 nutritional intake affects a person's immune system. To increase the acceptance of local products in the student environment, it is done by creating ginger and tempeh flour food bars which play a role in increasing the immune system. The purpose of this activity is to increase knowledge and train the skills of HMKG students. This activity will be held on March 21-22 2022. The venue for this activity is the Lubuk Pakam Medical Institute Campus. The target audience for this activity are active students of the Public Health and Nutrition Association (HMKG) of the Faculty of Public Health, Lubuk Pakam Medistra Health Institute, male and female, with a total of 20 participants. Based on the results of monitoring and evaluation during the socialization and education activities aimed at measuring success, it was found that before the socialization and education were carried out, the average student questionnaire results were 53.33 while after the activities had increased so that the average obtained was 86.66 from the maximum result was 100 points. based on the assessment of the attributes of texture, color, aroma and taste that the results of food bars products are group C. Based on the organoleptic assessment that the highest rating is on aroma. The aroma of the resulting product is the dominant aroma of ginger. Based on the results of this activity, it can be concluded that the HMKG students of the Mediatra Lubuk Pakam Health Institute as partners know the importance of maintaining and improving the body's immune system during the Covid-19 endemic period. In this activity, HMKG students experienced an increase in knowledge.